Two different hematocrit detection methods: Different methods, different results? - Bosshart, Marco (BioMed Central, 2010)
BACKGROUND: Less is known about the influence of hematocrit detection methodology on transfusion triggers. Therefore, the aim of the present study was to compare two different hematocrit-assessing methods. In a total of 50 critically ill patients hematocrit was analyzed using (1) blood gas analyzer (ABLflex 800) and (2) the central laboratory method (ADVIA(® )2120) and compared. FINDINGS: Bland-Altman analysis for repeated measurements showed a good correlation with a bias of +1.39% and 2 SD of ± 3.12%. The 24%-hematocrit-group showed a correlation of r(2 )= 0.87. With a kappa of 0.56, 22.7% of the cases would have been transfused differently. In the-28%-hematocrit group with a similar correlation (r(2 )= 0.8) and a kappa of 0.58, 21% of the cases would have been transfused differently. CONCLUSIONS: Despite a good agreement between the two methods used to determine hematocrit in clinical routine, the calculated difference of 1.4% might substantially influence transfusion triggers depending on the employed method.